Psychometric evaluation of the Chinese version of self-assessment scale for the community- based and emergency practice among medical students - Hu, Qi; Zheng, Chen; Yang, Xue (Frontiers in Public Health, 2025)
ObjectiveAs the population continues to age, community-based primary services and treatment for older people have become the most important part of the public health system. The aim of this study was to translate the Self-assessment scale for the community- based and emergency practice (C-CEP) into Chinese and to test its reliability and validity among medical students.MethodsAfter gaining access to the C-CEP scale, the Brislin translation-back translation model was used for translation and cross-cultural adaptation. 600 medical students were recruited to participate in this study using a convenience sampling method (n = 600). General information about the study population was analyzed by descriptive statistics; item analysis was used to screen the scale items; the reliability of the Chinese version of the questionnaire was measured by internal consistency, split-half reliability, and retest reliability; the validity of the questionnaire was measured by content validity and structural validity.ResultsThe English version of the C-CEP consisted of 15 items and the analysis of the items showed that all indicators were met. This study conducted an internal consistency test on the four dimensions and the total scale of the Chinese version of C-CEP. The Cronbach’s α of the four dimensions were 0.852, 0.886, 0.895, and 0.853 respectively, and the Cronbach’s α of the total scale was 0.933. The retest reliability was 0.754 and the split-half reliability was 0.883. The four-factor structure explained a cumulative 74.897% of the total variance. All the content validity was met. The model-fit indicators were all within acceptable limits.ConclusionThe Chinese version of the Self-assessment scale for the community- based and emergency practice had good reliability and validity and could effectively assess medical students’ self-practice skills. The Chinese version of the C-CEP is a reliable and valid tool for assessing medical students’ community and emergency practice self-efficacy. It can explore the direction of community practice education for medical students and improve their practical emergency response capabilities.